Characterization and Evaluation of Antioxidant activity of Crataeva magna Lour (DC) - RADHA krishnan meera (Journal of Global Pharma Technology, 2017)
Objective: The present study was designed to investigate the anti-oxidant activity of the ethanolic extract of Crataeva magna Lour DC. The root bark of Crataeva magna Lour DC belonging to family Capparaceae is used in anti spasmodic, hypotensive, anti-inflammatory, hypoglycemic, anti protozoal, analgesic purposes.Methods: The ethanolic extract was evaluated by TLC and the antioxidative potential of ethanolic extract of Crataeva magna Lour DC was evaluated using 1,1-Diphenyl-2-Picrylhydrazyl (DPPH), hydrogen peroxide and xanthine oxidase inhibition assay.Results: The ethanolic extract of Crataeva magna Lour DC exhibited highest level of antioxidant activities. The ethanolic extract of Crataeva magna Lour DC showed up to 76% inhibition of DPPH free radical at 517 nm at high concentration of 1 mg/ml. The in-vitro xanthine oxidase inhibition of root ethanolic extract revealed significant (69%) inhibitory activity at 30 µg/ml and it compared with the standard drug quercetin which showed 70% inhibition at 30 µg/ml. In hydrogen peroxide scavenging activity the test extract shows 26% of inhibition when compared to the standard ascorbic acid.Conclusion: The presence of strong antioxidant activity of ethanolic extract of Crataeva magna Lour DC can be a great scope for further studies on this plant regarding its antioxidant potentials.Keywords: Root bark of Crataeva magna Lour DC, TLC, Antioxidant activities.